(2a+b)^2-6a-3b-4 plz tell me the answerr
Answers
Answered by
3
(2a + b)² - 6a - 3b - 4
(2a + b)² -3(2a + b) - 4
Let (2a + b) = x
x² - 3x - 4
x² - 4x + x - 4
x(x - 4) +1(x - 4)
(x - 4)(x + 1)
(2a + b - 4)(2a + b +1)
I hope this will help you
(-;
(2a + b)² -3(2a + b) - 4
Let (2a + b) = x
x² - 3x - 4
x² - 4x + x - 4
x(x - 4) +1(x - 4)
(x - 4)(x + 1)
(2a + b - 4)(2a + b +1)
I hope this will help you
(-;
Answered by
3
Heya ✋
Let see your answer !!!!!!
![(2a + b) ^{2} - 6a - 3b - 4 \\ = (2a + b) ^{2} - 3(2a + b) - 4 (2a + b) ^{2} - 6a - 3b - 4 \\ = (2a + b) ^{2} - 3(2a + b) - 4](https://tex.z-dn.net/?f=%282a+%2B+b%29+%5E%7B2%7D++-+6a+-+3b+-+4+%5C%5C++%3D+%282a+%2B+b%29+%5E%7B2%7D++-+3%282a++%2B++b%29+-+4)
![putting \: (2a + b) = y putting \: (2a + b) = y](https://tex.z-dn.net/?f=putting+%5C%3A+%282a+%2B+b%29+%3D+y)
Hence ,
![y ^{2} - 3y - 4 \\ = y ^{2} - 4y + y - 4 \\ = y(y - 4) + 1(y - 4) \\ = (y - 4)(y + 1) \\ = (2a + b - 4)(2a + b + 1) y ^{2} - 3y - 4 \\ = y ^{2} - 4y + y - 4 \\ = y(y - 4) + 1(y - 4) \\ = (y - 4)(y + 1) \\ = (2a + b - 4)(2a + b + 1)](https://tex.z-dn.net/?f=y+%5E%7B2%7D++-+3y+-+4+%5C%5C++%3D+y+%5E%7B2%7D++-+4y+%2B+y+-+4+%5C%5C++%3D+y%28y+-+4%29+%2B+1%28y+-+4%29+%5C%5C++%3D+%28y+-+4%29%28y+%2B+1%29+%5C%5C++%3D+%282a+%2B+b+-+4%29%282a+%2B+b+%2B+1%29)
Thanks :)))))
Let see your answer !!!!!!
Hence ,
Thanks :)))))
Similar questions